2014
DOI: 10.1007/s00535-014-0932-4
|View full text |Cite
|
Sign up to set email alerts
|

Antitumor function of microRNA-122 against hepatocellular carcinoma

Abstract: MicroRNA-122 (miR-122), a highly abundant and liver-specific miRNA, acts as a tumor suppressor against hepatocellular carcinoma (HCC). Decreased expression of miR-122 in HCC is frequently observed and is associated with poor differentiation, larger tumor size, metastasis and invasion, and poor prognosis. Mutant mice with knockout

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
98
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 126 publications
(103 citation statements)
references
References 44 publications
4
98
0
1
Order By: Relevance
“…MiR-122 acts as a tumour suppressor by binding to target genes involved in cell proliferation, migration, differentiation, apoptosis and angiogenesis (Nakao et al, 2014). MiR-122 is dramatically downregulated in most HCCs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…MiR-122 acts as a tumour suppressor by binding to target genes involved in cell proliferation, migration, differentiation, apoptosis and angiogenesis (Nakao et al, 2014). MiR-122 is dramatically downregulated in most HCCs.…”
Section: Discussionmentioning
confidence: 99%
“…Further, overexpression of miR-122 reduces tumorigenic properties of HCC cells, indicating that it acts as tumour suppressor (Bai et al, 2009). Some of the miR-122 targets are involved in cell proliferation, differentiation, apoptosis, and angiogenesis (Xu et al, 2012;Nakao et al, 2014). Although miR-122 expression is reduced in HCC, the mechanism of this down-regulation is still unclear.…”
Section: Introductionmentioning
confidence: 94%
“…Down-regulation of miR-452 has been associated with promoting stem-like traits and tumorigenesis of gliomas and it has been suggested that it may represent a novel prognostic biomarker and therapeutic target for the disease [62]. In addition, miR-122, has been well-documented to act as tumor-suppressor gene for hepatocellular carcinoma [63,64] and breast cancer [65]. Regarding brain tumors, under expression of miRNA-122 has been demonstrated in glioma specimens and glioma cell lines and has been inversely correlated with patients’ survival following surgery [66].…”
Section: Discussionmentioning
confidence: 99%
“…Although it is expressed abundantly in mouse and human liver cells, it has a very low level of expression in most tissues [21] . miR-122 plays a critical role in regulating hepatocyte development and differentiation, lipid metabolism, as well as stress response [22] . Tsai et al used a computational approach and identified multiple miR-122 candidate target genes from two independent expression microarray datasets in an orthotopic HCC model in vivo with tumorigenesis, angiogenesis and intrahepatic metastasis, proving that liver-specific miR-122 is significantly down-regulated in HCC with intrahepatic metastasis, and negatively regulates tumorigenesis by targeting ADAM17 [23] .…”
Section: Mir-122mentioning
confidence: 99%